The Homomorphisms and Operations of Rough Groups - Fei Li; Zhenliang Zhang (The Scientific World Journal)
Based on the light relation between a normal subgroup and a complete congruence relation of a group, we consider the homomorphism problem of rough groups and rough quotient groups and investigate their operational properties. Some new results are obtained.